An analysis of the effects of budgetary process and control on performance of manufacturing companies : a case of MegaPak Pvt Ltd - Chimbalami, Patricia (2020)
The recurring adverse overhead expenditure variances between 2015 and 2017 reaching a peak of USD509 798 in 2016 at Mega Pak Pvt Ltd has triggered the researcher to analyse the effects of budgetary process and control on performance of manufacturing companies in Zimbabwe with special focus on Mega Pak Pvt Ltd. Specifically the study sought to identify the effects of budget process and control on organisational performance and to identify factors that affect the budgetary process at Mega Pak Pvt Ltd. The study also aimed at identifying the limitations faced by Mega Pak Pvt Ltd in relation to the budgetary process and budgetary control. Finally, the study sought to identify ways to improve budgeting and budgetary controls at Mega Pak Pvt Ltd. The researcher used the mixed method approach to conduct the study. A questionnaire and a semi-structured interview were triangulated to collect data from participants. A sample of sixty participants was sampled using stratified random sampling and simple random sampling from a population of two hundred and eighty seven employees at Mega Pak Pvt Ltd. A response rate of questionnaires obtained was 83%. The study found out that the effects of budget process and control on performance of Mega Pak Pvt Ltd entail provision of expenditure tracking and reduction of operational costs. The researcher concluded that the top five effects of budget process and control on performance entail provision of expenditure tracking and reduction of operational costs, enhancement of performance evaluation, and effective tool for resource allocation, facilitation of business growth and promotion of goal congruence at the organization. The researcher also concluded that both internal and external factors affect the budgetary process at Mega Pak Pvt Ltd. It was also concluded that Mega Pak Pvt Ltd faced a myriad limitations that included time constraint in budget preparation, inadequate financial resources to finance budgetary process, hindering of initiative and lack of training to budget implementers. The study recommended a move to beyond budgeting, training of employees on budget preparation, process, implementation and use of advanced budgeting software.